Design of real-time monitoring and intelligent management cloud platform for entire process of construction waste. Issue 2 (August 2019) - Wang, Fujun; Ding, Cong; Liu, Dongfusheng; Bi, Jun
Abstract: In order to achieve real-time detection and intelligent control of generation links, transportation processing links, resource utilization and application of recycled products about construction waste, the real-time monitoring and intelligent control cloud platform is studied. This platform can dock urban external construction departments, urban management departments and other external e-government systems to achieve the aims of entire process detection and intelligent resource utilization. This paper studies the design and implementation of real-time monitoring and intelligent control cloud platform for construction waste. This platform is divided into three parts: the data acquisition layer, the data transmission layer, the big data processing layer and application service layer. The article focuses on the functions and technical implementation of each layer: data access design including big data monitoring technology in the whole process of construction waste control, storage design of cloud computing collaborative service technology in the whole process of construction waste control, real-time 3D visualization software and hardware support based on space-time cloud platform.